Peningkatan Hasil Belajar PAK melalui Model PBL Berbasis Canva di SDN Saloo Hilina’a - Agustinus Zebua; Ansel Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This research was motivated by the low learning outcomes of students in Catholic Religious Education (PAK) at SDN Saloo Hilina’a, which is attributed to the lack of innovative learning media used by educators. The study, titled "Improving PAK Student Learning Outcomes with PBL Learning Canva Application in Class IV of SDN Saloo Hilina’a, North Nias Regency", aims to determine whether the Problem-Based Learning (PBL) model using the Canva application can improve student learning outcomes. This classroom action research (CAR) was conducted in two cycles. The first cycle implemented conventional learning without the PBL method, while the second cycle applied the PBL approach supported by the Canva application. Canva is a digital tool that allows the creation of various learning materials such as greeting cards, posters, brochures, infographics, and presentation media. In the second cycle, the integration of PBL with Canva media increased student engagement and participation in the learning process. The results showed a significant improvement in student learning outcomes and enthusiasm from cycle to cycle. The study concludes that the use of the PBL model supported by Canva can effectively enhance student activeness and learning outcomes in PAK subjects. This combination serves not only as a visual support tool but also helps students develop visual literacy skills relevant to the digital era, thereby making learning more interactive, creative, and student-centered.